A COMPARATIVE STUDY OF INFLAMMATORY MARKERS LEVELS IN PATIENTS OF TUBERCULOSIS AND COVID-TB COINFECTION - APARAJITA KUSHWAHA; SOHIL TAKODARA; NEHA SHARMA; BADRI LAL JAT; RAJU RAM (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The outbreak of COVID-19 has increased the vulnerability of global population to diseases; above all, the patients suffering from tuberculosis (TB) COVID-19. Both being diseases of the respiratory tract, a confection of the two might cause severe implications. The WHO has set a goal of eradicating TB globally by the year 2035 (END-TB program). To achieve this goal, various initiatives are being taken with respect to early diagnosis, screening – research and development of new diagnostic as well as treatment tools. Although, the pandemic largely interrupted these initiatives setting back progress by approximately a decade; it should not be overlooked that COVID-19 has unlocked new doors to research and development in the niche of infectious diseases. This study was aimed at analyzing of inflammatory markers in patients of TB, COVID-19, and COVID-TB confection. Methods: A total of 164 patients aged between 18 years to 85 years were included in this study. Total patients (164) were, then, divided into three groups on the basis of their disease diagnosis. The patient groups are as follows: 57 COVID-19-positive patients, 53 COVID-TB coinfection-positive patients, and 54 TB-positive patients. Serological analysis data of C-reactive protein (CRP), D-dimer, and SGOT were statistically analyzed using one-way ANOVA. Results: The results of analysis of variance showed significant results for all three inflammatory markers with p<0.05. The levels of CRP, D-dimer, and SGOT underwent the highest increase among COVID-TB coinfection patient. Conclusion: Through this study, it can be concluded that the addition of inflammatory markers testing in TB patients and diagnostic protocols may prove to be of significant assistance in diagnosis of TB and also to estimate the severity of infection in patients of active TB. It is also noteworthy that the levels of these markers were found to be highest in patients suffering from a coinfection of both the diseases.